PENGARUH MEKANISME BONUS, UKURAN PERUSAHAAN, LEVERAGE, DAN MULTINATIONALITY TERHADAP KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Rezky, Machfirah Aprilia; Fachrizal, Fachrizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The research examines the effect of bonus mechanism, firm size, leverage, and multinationality on transfer pricing decision of manufacturing companies listed in Indonesia Stock Exchange in 2010-2014. Secondary data were sourced from the financial statements, published by the capital market reference center at the Indonesia Stock Exchange. The research type used in this research is hypothesis testing, by using purposive sampling method. There are 75 samples of the data that become the object to be researched. This research uses logistic regression analysisto test the hypothesis. The results of this research show that simultaneous of bonus mechanism, firm size, leverage and multinationality have effect on transfer pricing decision. Partially the research shows that (1) bonus mechanism have positive effect on transfer pricing decision, (2) firm size have positive effect on transfer pricing decision, (3) leverage have positive effect on transfer pricing decision, and (4) multinationality have positive effect on transfer pricing decision.